Electrical Properties of Microporous Carbon from Biomass Wood; Tamarind, Mahogany, Teak, and Coconut Shell: M Mashuri, Cindy C Karim, A Fauziyah, S Suyatno - Mashuri Mashuri; Cindy C. Karim Cindy C. Karim; A. Fauziyah A. Fauziyah; Suyatno Suyatno (Jurnal Fisika dan Aplikasinya, 2024)
Microporous carbon has been successfully synthesized from biomass, namely Tamarind Wood (Tamarindus Indica), Mahogany Wood (Swietenia Mahagoni), Teak Wood (Tectona Grandis), and Coconut Shell (Cocos Nucifera). Microporous carbon was synthesized using the carbonization method at 600°C for 45 minutes and washed using an ultrasonic cleaner for 6 hours. Next, the micro-porous carbon powder is dried in the sun and grinded mechanically. Microporous carbon powder was characterized by phase, average particles size, gap energy and electrical conductivity using XRD, PSA, UV-vis and LCR meters. The characterization results show that microporous carbon in the rGO (reduced graphene oxide) phase with a (002) reflection plane in an amorphous carbon graphite structure, the average particle size of Tamarind Wood (8.068 µm), Mahagony Wood (4.409 µm), Teak Wood (3.902 µm) and Coconut shell (3.653 µm). The gap energy measurement results show respectively 1.491 eV, 1.771 eV, 1.821 eV and 2.342 eV with an electrical conductivity value of 142.1×10-2 S/m, 1.281×10-2 S/m, 0.962×10-2 S/m, 0.771×10-2 S/m respectively Coconut shell, Teak Wood, Mahogany Wood, and Tamarind Wood. This microporous carbon-based wood biomass is semiconductors that have the potential as environmentally friendly energy storage supercapacitor materials.